Os efeitos de uma intervenção, segundo o conceito de Bobath, na função motora, em crianças com paralisia cerebral - Mafalda Santos Lobato (Sociedade Brasileira de Pediatria, 2022)
The aim of this study was to assess the effects of an intervention in the light of the Bobath concept on motor function, in children with cerebral palsy. This is a systematic literature review that includes nine studies published between 2014 and 2019, and those were researched in three distinct databases: B-On; PubMed; ScienceDirect. The nine studies contemplated are indicative of the positive effects of the Bobath concept on the motor function of children with cerebral palsy, as well as on visual attention, contributing to the improvement and increase in the quality of life and independence in the daily living activities of these children. We concluded that the Bobath concept should integrate the physical therapy intervention which aims to improve the motor function of children with cerebral palsy. However, it is necessary to mention the need to carry out more studies that focus not only on the concept of Bobath, but also on the effects produced in motor function in this specific population.